Mismeasurement in pay-for-performance: Evidence from an intervention to reduce health care spending in China - Bingxiao Wu (Rutgers University, Department of Economics, 2014)
This paper examines how physicians in China respond to a pay-for-performance scheme that mismeasures performance. In 2005, China imposed a policy that penalizes hospitals with high drug sale percentage in the total revenue, with the intent to decrease drug expenditure. Using a unique patient-level data from a large Chinese hospital, I find that physicians responded not by decreasing drug prescription, but by increasing non-drug services, especially diagnostic tests. There is no significant impact on length of stay. The overall effect was to increase total expenditures. This finding is consistent with the inducement hypothesis as physicians in China may receive under-the-counter commission for prescribing certain drugs. I also find that increased non-drug expenditures were concentrated among insured patients, suggesting that physicians have stronger incentives to act in the patients interests than in the interests of the third-party payer.
Keywords: I11; I18; M52; 330; pay-for-performance; physician incentives; drug prescription; Chinas health care system